(3CUhd GdJCejf (B:s (3OQGSI ebGQfI ddJTQjY hGdabg hGdbVGA (B/s - (3GdLeGd, eUWai eMeOs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 1999)
(3ebheGJ GdJCejf(B- (3BKGQ GdJCejf(B.s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3YbO GdVeGfs